Transforming the Teaching and Learning Practice in South Africa by Integrating Bapedi Spiritual Folk Songs (Choruses) into Curriculum - (:unkn) unknown (My University, 2024)
This book chapter considers the recontextualization of traditional Bapedi religious songs in formal South African curricula. The Bapedi is an ethnic group in South Africa whose traditional religious music is not well-documented. This study collected and analyzed thirty-one traditional Bapedi spiritual folk songs (choruses) from eleven elderly Bapedi women in Greater Sekhukhune District Municipality, Limpopo Province, South Africa and discussed the transformation of teaching and learning practice. The main aim of this study was to analyze these songs using religious, musicological and contextual perspectives. In this context, two spiritual folk songs (choruses) were selected. Eight Sepedi-speaking children from a school choir at Baxoxele Primary School in Soshanguve were observed while learning these two spiritual folk songs (choruses). It has emerged from this study that repetition was used as a powerful, rhetorical and expressive device skilfully employed to express and internalize the faith and to impart dominant emotions. Informal discussions with teachers indicated that the children improved in their concentration and attitude toward schoolwork. During interviews and observations, it was also established that learning these two choruses also unlocked some creative talent and improved their social skills. Other benefits included improved social skills. The results have shown that the joyous nature, rhythmic foundation, harmonic simplicity and combination of intellect and emotion as well as the repetitiveness and briefness of these songs appealed to both children and adults. It was concluded that for the preservation of traditional Bapedi religious music and culture, there is an urgent need for the collection and documentation of traditional Bapedi religious songs. In recognizing their identity, such songs could contribute to the attitudes and cultural values of Sepedi-speaking children. For the preservation of African cultural heritage and identity,
Keywords: African Research